Analisa Opini Hasil Audit BPK pada Laporan Keuangan Lembaga Negara terhadap Kualitas Penyelenggaraan Lembaga Negara Menggunakan Content Analysis (Studi Kementerian Negara di Indonesia Tahun 2012-2016) - Putra, Yananto Mihadi (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2018)
The purpose of this study is to know and analyze the accounts that are excluded, there are problems in the accounts is excluded, and the cause of the problems contained in the accounts are exempt from the examination report on the financial statements of ministries/agencies with the exception of obtaining reasonable opinion. This research uses a qualitative research methodology approach based positivistic philosophy. The data analysis in this research using content analysis with the type of conceptual analysis or collectively, the descriptive content analysis. The results showed that problems in the accounts that are excluded and the associated restrictions on the scope of noncompliance with Generally Accepted Accounting Principles (GAAP). The cause of the problems contained in the accounts that are excluded is due to the weakness of internal controll and non-compliance with laws and regulations. Internal controll weaknesses include a lack of commitment to competence, leadership is not conducive, the lack of delegation of authority and responsibility for the proper, good working relationships with relevant government agencies have not been optimal, the weakness of the organizational structure, purpose of activity is not supported enough resources, internal control weaknesses the application of the SAI, physical control over assets and records have not been optimal, there is no verification process to the evidence of payment, expenditure, and accountability, which have incomplete information, and recommendations not yet acted upon the findings of the previous year.